ANALISIS KINERJA KEUANGAN KOPERASI UNIT DESA DI KABUPATEN KAMPAR - Rahmad Danel; Caska Caska; Makhdalena Makhdalena (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This study aims to determine the level of financial performance of Cooperatives in Kampar Regency Village Unit views of the financial statements based on financial ratios Liquidity, Solvency, and Profitability. This study in village cooperatives located in Kampar District, amounting to 24 units of village cooperatives. The data collection technique is to use the financial statements of the Kampar district cooperative offices. The analysis technique used is a financial ratio analysis. the results showed: 1) the level of liquidity unfavorable 7.17% -185%. 2) the level of solvency is less baik112, 31% -471.55%. 3) the level of capital itself shows baik371 conditions, 55% -1.93%. 4) the rate of return on assets indicates a good condition 21.61% -0.10%. 5) rates of return of capital alone showed a good condition 54.93% -1.67%.Keywords: performance, financial reports and financial ratios